Countering Illegibility: A Brief History of Forced Evictions in Postsocialist Romania - Zamfir George Iulian (Studia Universitatis Babes-Bolyai Sociologia, 2022)
Forced evictions have been recognised as a relevant process in Romanian post-socialist urban transformations. Housing privatization, including restitutions, represents the key driver. Some attempts in grasping the scale of the process have already been made. This article brings extensive quantitative data stemming from national and local levels, which can support improved estimations of the scale: reports of the National Union of Bailiffs and answers to public information requests from multiple municipalities; archival data, local press monitoring and accounts of the process in the city of Cluj-Napoca. At least 100 thousand forced evictions are estimated to have taken place at national level between 1990-2017, comprising several hundred thousand individuals, the Roma population being disproportionately affected. Qualitative data produced through activist research complements the picture. The findings contribute to the debate regarding postsocialist urban transformations, indicating that the role of the state in the production of the housing market through forced evictions-based gentrification has been insufficiently acknowledged. The results are relevant to policy debates, as well as to housing activist practices2.